Exile on the Paths of Hope - Somr, Miroslav (Wydawnictwo Naukowe UAM, 2013)
Comenius called Poland his second motherland. Rightfully so. He was connected to the Polish reality not only through the long period of life he spent there but also through his thinking activity, when he was occupied between the years 1628–1656 that he (intermittently) lived in Poland with efforts to improve the circumstances into which his home country was plunged due to the counter- Reformation oppression that followed the catastrophe in the wake of the White Mountain battle defeat.
Wygnanie na ścieżkach nadziei
Keywords: Leszno; Excidium Lesnae; colloquium charitativum; Bartoloměj Nigrinus; Sádovský family; market of the world